FACTORS AFFECTING THE INTEGRITY OF THE AUDITEE FINANCIAL STATEMENT WITH THE MEDIATION VARIABLE: AUDIT QUALITY - Ayu Nurvita Sari; Ridwan Saleh; Ramdany; Samukri (Asosiasi Dosen Muda Indonesia, 2023)
The integrity of the auditee's financial reports is still an issue and a concern, because there are many cases of manipulation of accounting data. This is caused by various factors, both internal factors and external factors. This study only focuses on external factors, namely audit quality, which will be used as a mediating variable. The research objective is to find out empirical evidence of the effect of auditor integrity, auditor experience, obedience pressure, professional development on audit quality, audit quality on the integrity of auditee's financial statements, audit quality can mediate the relationship between auditor integrity, auditor experience, obedience pressure, professional development on integrity audited financial reports. This study uses primary data and is measured by a Likert scale of 5. The sample uses a nonprobability sampling technique and the accidental sampling method with a total of 100 auditors in DKI Jakarta. Data analysis using Partial Least Square (PLS). The results of this study indicate that auditor integrity, obedience pressure and professional development have a significant positive effect on audit quality, auditor experience has no significant effect on audit quality, audit quality has a significant positive effect on the integrity of the auditee's financial statements. Auditor integrity, obedience pressure and professional development have a significant positive effect on the integrity of the auditee's financial statements qthrough audit quality, but the auditor's experience has no significant effect on the integrity of the auditee's financial statements through audit quality.